Blind data recovery of single-channel mixed signals based on Turbo equalization and channel estimation - Dong-ling ZHANG; Yong YANG; Jing LI; Lin-dong GE (Tongxin xuebao)
The timing synchronization is the key technique of the single-channel blind signal receiver.The single-channel blind recovery algorithm based on Turbo equalization was proposed,which does not require the timing synchronization.In the algorithm,the timing offset is taken as inter-symbol interference channel,which can improve the restorability of source signals by the feedback soft information between channel estimation and the turbo equalization.The primary works include the research on initial blind equalization algorithm,the channel estimation algorithm,MMSE equalization algorithm for the mixed signals and the soft information interaction among those three algorithms.The proposed algorithm has low computational complexity and small computational load,which can be applied to high-order modulated signals.Simulation results show that,good performance could be achieved for BPSK,QPSK and 8PSK modulated signals.In addition,the proposed algorithm is suitable for both equal power and unequal power signals.